PERAN MAHASISWA PRAKTIK PENGALAMAN LAPANGAN (PPL) DALAM MENDUKUNG KEGIATAN PEMBELAJARAN DAN NONPEMBELAJARAN DI MAS AL-MANDILY - Fatimah Hannum; Hafizah Hapsani; Elvina Lbs; Khoirun Nisah Nasution; Rizki Hasanah Lubis; Nurul Hidayah; Nur Asyah Lubis; Khairul Bahri Nasution (STKIP Pesisir Selatan, 2026)
This study aims to explain the role of students participating in the Field Experience Program (PPL) in supporting both learning and non-learning activities at MAS Al-Mandily. The PPL program serves as a platform for students to apply theoretical concepts learned at the university through direct involvement in educational activities at the school. The findings indicate that PPL students contribute significantly to the learning process, including lesson planning, selection and preparation of teaching media, conducting teaching sessions, guiding students, and carrying out learning assessments. Moreover, PPL students also participate in various non-learning activities such as school administration, extracurricular assistance, discipline development, and social and religious programs. The presence of PPL students brings positive impacts to students, teachers, and the institution by increasing learning motivation, supporting classroom management, assisting administrative processes, and strengthening collaboration between the madrasah and higher education institutions. In addressing challenges during the PPL implementation, students undertake several efforts such as consulting with supervising teachers, improving teaching preparation, understanding student characteristics, and establishing effective communication with the school. Overall, the implementation of the PPL at MAS Al-Mandily provides significant benefits for both students and the institution, and plays an essential role in preparing professional and competent future educators.